Duo sang Tōsan - Wu, Nianzhen; Li, Hongqin (Da la chu ban gu fen you xian gong si, 2015)
Father was born in the Japanese colonial era. He was called by his Japanese name, Sega. He has never forgotten those good old days. He still thinks, everything made in Japan is the best, and his fondest dream as an old man is to go to Japan and see Mount Fuji and the Imperial Palace. Sega represents an entire generation of Taiwanese men. They are masculine and practical, they love their wives and children, but they can never bring themselves to say it. They only show it through their hard work in raising their children to adulthood. For that generation, they face the difficulties not just of daily life, but also of cultural identity. A father who speaks only Taiwanese and Japanese naturally cannot fit in with the values of his Chinese-educated children. The decline of the mining industry forces the family to move to Ruifang, and Sega no longer has regular work. His wife is forced to work odd jobs to support the family. In his fifties he falls to lung illness because of his work in the mines, and he goes in and out of the hospital, the devil-may-care attitude of his youth slowly erodes ... Adapted from Wu Nien-jen's film "A borrowed life", this book is a true-to-life record of the life of Wu's own father as well as all the other fathers of that generation. Li Hung-tsin's image compositions tend to use the visual language of film, his perspectives working more like a movie camera than traditional comic compositions. He "cuts" between characters in dialogue, and creates a strong sense of atmosphere through his art. He starts with pencil before using ink and dot shading to achieve his vital and lively style amidst a naturalistic and fine-tuned approach.
Based on the film by Wu Nien-jen, Comics art by Li Hung-tsin
Keywords: Manners and customs; Kulturelle Identität; Mann; Taiwan / History / 1945-1975; Taiwan / Social life and customs / 1975-; Taiwan; Comic